COMPARATIVE ANALYSIS OF STUDENT CHARACTER FORMATION THROUGH CHOIR EXTRACURRICULAR PROGRAMS AT SD MARSUDIRINI BSB AND SD NURUL ISLAM SEMARANG: ANALISIS PERBANDINGAN PEMBENTUKAN KARAKTER PESERTA DIDIK MELALUI PROGRAM EKSTRAKURIKULER PADUAN SUARA DI SD MARSUDIRINI BSB DAN SD NURUL ISLAM SEMARANG - Muhammad Alif Jauhar Habib; Arsan Shanie (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Student character is still a challenge in elementary education, especially related to discipline, responsibility, and cooperation. This study aims to analyze and compare the role of extracurricular choir programs in character building for students at SD Marsudirini BSB Semarang and SD Nurul Islam. This study uses a descriptive qualitative approach with a case study method. Data were collected through observation, interviews, and documentation of students, teachers, coaches, and parents. Although both schools have extracurricular choirs, there are differences in intensity, technicalities, program achievements, and support and parental involvement that affect the results of character building for students. The results of the study indicate that the choir program has a significant impact on strengthening student character, especially in terms of discipline, cooperation, and responsibility. Differences in program implementation and intensity in both schools provide variations in student character outcomes. Structured practice activities and teamwork encourage students to build positive attitudes, such as valuing time and personal responsibility. . This study concludes that choir is an effective means of instilling character values ​​in elementary schools and can be a contextual character building model.